PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, SUPERVISI AKADEMIK, DAN BUDAYA SEKOLAH TERHADAP KINERJA GURU DI SD SE-KECAMATAN KANGKUNG DENGAN MOTIVASI KERJA SEBAGAI MEDIATOR - Moga Prastyowati; Widiyanto; Sugi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of transformational leadership, academic supervision, and school culture on the performance of elementary school teachers in Kangkung District, with work motivation as a mediating variable. The research employed a quantitative approach using regresion, path analysis and the Sobel test to examine both direct and indirect effects. A total of 141 teachers were selected through simple random sampling. The results indicate that academic supervision and school culture have a significant positive effect on both work motivation and teacher performance, directly and through the mediation of work motivation. School culture emerged as the most influential variable on work motivation. Meanwhile, transformational leadership had a significant negative effect on work motivation and no significant effect on teacher performance, either directly or indirectly. Work motivation was proven to be an effective mediator in strengthening the influence of academic supervision and school culture on teacher performance. This study highlights the importance of work motivation and a positive school environment in improving teacher performance.